Adaptive Non-Deterministic Decision Trees: General Formulation and Case Study - Pistori, Hemerson; Neto, João José; Pereira, Mauro Conti (INFOCOMP Journal of Computer Science, 2006)
This paper introduces the adaptive non-deterministic decision tree, a formal device derived from adaptive device theory. ANDD-tree is a new framework for the development of supervised learning techniques. The general formulation of this framework, a case study and some experimental results are also presented.